A STUDY ON PROBLEM SOLVING ABILITY AMONG STUDENTS OF GOVT. SENIOR SECONDARY SCHOOL : A COMPARATIVE ANALYSIS - Arora, Triptjit Kaur (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Problem-solving ability is a crucial skill that is essential in many areas of life, including education, job, and daily decision-making. Problem-solving ability is a multidimensional cognitive skill that entails recognizing, analyzing, and addressing problems in a variety of circumstances. Problem-solving abilities are required to navigate the intricacies of everyday life, from calculating mathematical calculations to resolving interpersonal conflicts. Problem-solving ability is a critical cognitive skill that allows people to navigate the problems and hurdles that arise in diverse settings. Problem-solving abilities are essential for success in education, work, and daily life, ranging from solving mathematical equations to resolving interpersonal conflicts. The importance of problem-solving ability for students cannot be overstated, as it is a critical skill that transcends academic disciplines and is vital for success in various aspects of life. The purpose of this study was also to analyse the problem solving ability of higher secondary school students of Arts and Commerce stream. For this purpose, the sample was consisted of 80 students. Out of 80 students, 40 were from Arts and 40 were from commerce stream taken. Problem Solving Ability Test (PSAT) developed by L.N. Dubey was used as a tool for data collection. Mean and t-test were used to analyse the data.